Women, Partners, and Mothers-Migratory Tendencies of Psychiatric Trainees Across Europe - Mariana Pinto da Costa; Mariana Pinto da Costa; Mariana Pinto da Costa; Ana Giurgiuca; Eirini Andreou; Franziska Baessler; Visnja Banjac; Ewelina Biskup; Ewelina Biskup; Jozef Dragasek; Emam El-Higaya; Kfir Feffer; et al. (Frontiers Media S.A., 2019)
Introduction: Combining a successful career with family planning has become increasingly important in recent years. However, maintaining a relationship, deciding upon the optimal time for pregnancy and other family planning decisions can still be quite challenging, especially for junior doctors whose training is long and demanding. Currently, women form an important part of the medical workforce, and there is noticeable feminization in migration. However, little is known about the personal characteristics of junior doctors in Europe and how these play a role in their decision to migrate.Methods: Survey of psychiatric trainees in 33 European countries, exploring how personal characteristics, such as gender, relationship status and parenthood, impact their attitudes toward migration.Results: 2,281 psychiatric trainees in Europe took part in the study. In this sample, the majority of psychiatric trainees were in a relationship, but only one quarter had children, although there were variations across Europe. Both men and women indicated personal reasons as their top reason to stay. However, women ranked personal reasons as the top reason to leave, and men financial reasons. Single woman were the most likely of all subgroups to choose academic reasons as their top reason to leave. Interestingly, when women were in a relationship or had children, their attitudes toward migration changed.Conclusions: In this study, a low number of psychiatric trainees in Europe had children, with differences across Europe. These findings raise awareness as to the role of parental conditions, which may be favoring or discouraging parenthood in junior doctors in different countries.